A Phase Ib/II study of IGF-neutralising antibody xentuzumab with enzalutamide in metastatic castration-resistant prostate cancer - Macaulay, Valentine M; Lord, Simon; Hussain, Syed; Maroto, José Pablo; Jones, Robert Hugh; Climent, Miguel Ángel; Cook, Natalie; Lin, Chia-Chi; Wang, Shian-Shiang; Bianchini, Diletta; Bailey, Mark; Schlieker, Laura; et al. (British journal of cancer, 2023)
This multicentre, open-label, Phase Ib/II trial evaluated the insulin-like growth factor (IGF) 1/2 neutralising antibody xentuzumab plus enzalutamide in metastatic castrate-resistant prostate cancer (mCRPC). The trial included Phase Ib escalation and expansion parts and a randomised Phase II part versus enzalutamide alone. Primary endpoints in the Phase Ib escalation, Phase Ib expansion and Phase II parts were maximum tolerated dose (MTD), prostate-specific antigen response and investigator-assessed progression-free survival (PFS), respectively. Patients in the Phase Ib escalation and Phase II parts had progressed on/after docetaxel/abiraterone. In the Phase Ib escalation (n = 10), no dose-limiting toxicities were reported, and xentuzumab 1000 mg weekly plus enzalutamide 160 mg daily (Xe1000 + En160) was defined as the MTD and recommended Phase 2 dose. In the Phase Ib expansion (n = 24), median PFS was 8.2 months, and one patient had a confirmed, long-term response. In Phase II (n = 86), median PFS for the Xe1000 + En160 and En160 arms was 7.4 and 6.2 months, respectively. Subgroup analysis suggested trends towards benefit with Xe1000 + En160 in patients whose tumours had high levels of IGF1 mRNA or PTEN protein. Overall, the combination was well tolerated. Xentuzumab plus enzalutamide was tolerable but lacked antitumour activity in unselected patients with mCRPC. EudraCT number 2013-004011-41.